Detection of the human papillomavirus 58 physical state using the amplification of papillomavirus oncogene transcripts assay - Chaiwongkot A. (2014)
HPV 58 is detected commonly in cervical cancer in East Asian countries. To evaluate the HPV 58 physical state, the amplification of papillomavirus oncogene transcripts (APOT) and hybridisation assays were established. Episome- and integrate-derived transcripts were confirmed by direct sequencing. Twenty-nine HPV 58 positive samples from various cervical lesions were used. The results showed that the episome-derived transcripts were recognised as two major specific amplified products (1040 and 714. bp). Two splice donor sites were mapped to the 5' splice site of the E1 gene on SD898 and SD899 and spliced to the 3' acceptor site of the E4 gene on SA3353, SA3356 and SA3365. The episome-derived transcripts were found 100% in normal cervical epithelia and low-grade lesions (9/9 cases) while the integrate-derived transcripts were detected in 13.3% of high-grade lesions (2/15 cases) and in 20% of carcinomas (1/5 cases). HPV 58 integration sites were found on chromosomes 4q21, 12q24 and 18q12. Using the established APOT assay, the results revealed not only novel information on the HPV 58 transcription patterns of episomal transcripts, but also integration site. The APOT assay is a reliable and useful tool for the detection of the HPV 58 physical state and its oncogene expression. © 2013 Elsevier B.V.